The Integration ESD and Ethnoscience to Merdeka Curriculum: Study on Junior High School - Puspita, Gita Nurul; Widodo, Ari; Sriyati, Siti; Samsudin, Achmad (UIN Fatmawati Sukarno Bengkulu, 2024)
This research explored the implementation of ESD and ethnoscience-integrated learning in the Merdeka Curriculum at the junior high school in Cimahi City. Seventy out of 113 junior high school science teachers participated in this survey. Data collection was conducted using questionnaires followed by semi-structured interviews. Questionnaire data analysis employed percentage calculation techniques, while interview data were analyzed through data reduction, data presentation, and conclusion. It is found that 92.9% of teachers still need help understanding ESD and SDGs. Then, 95.7% of teachers know the benefits of connecting subject matter with students' socio-cultural environment, but they still need to understand ethnoscience. Only 7.1% of teachers have implemented ESD-integrated science learning, and 55.7% have implemented the Projects to Strengthen Pancasila Student Profile on Sustainable Lifestyle Theme in their schools. Only 4.3% of teachers have implemented ethnoscience-integrated science learning. The number of teachers who have implemented the Projects to Strengthen Pancasila Student Profile on Local Wisdom Theme is 60%. The main obstacle 90.2% of teachers face in implementing ESD-integrated science learning is that they still need to understand ESD and SDGs. Then, the main obstacle 92.9% of teachers face in implementing ethnoscience-integrated science learning is the difficulty in identifying local wisdom.